(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This research investigates the socioeconomic impact of colonialism through a comparative analysis of British colonial policies in India and resource-rich African nations. It explores the historical roots and economic motives behind colonial expansion, examining the differences between colonialism and imperialism. The study delves into the economic exploitation of colonies, highlighting the extraction of resources, establishment of trade monopolies and the impact of mercantilist policies. It also addresses the cultural consequences of colonial rule, including the imposition of European languages and the destruction of indigenous traditions. Politically, the research covers the governance structures imposed by colonial powers and the resistance movements that led to decolonization. Finally, the paper explores the contemporary effects of colonialism, including ongoing political conflicts, economic dependencies, and social imbalances in post-colonial states. The study aims to connect historical colonial practices with their modern-day repercussions, offering insights into the lasting legacies of colonialism on global power structures.